2020
DOI: 10.1021/acs.jafc.9b05966
|View full text |Cite
|
Sign up to set email alerts
|

Surface Activity of Alkoxy Ethoxyethyl β-d-Glucopyranosides

Abstract: Dioxyethene fragment (−(OCH2CH2)2−) was introduced into traditional alkyl β-d-glucopyranosides to ameliorate the water solubility, and eight nonionic surfactants, that is, alkoxy ethoxyethyl β-d-glucopyranosides with alkyl chain lengths (n = 6–16), were synthesized and characterized. Their hydrophilic and lipophilic balance number, water solubility, critical micelle concentration (cmc), γcmc, Γmax, and hygroscopic rate decreased with an increase in the alkyl chain length. Hexadecoxy ethoxyethyl β-d-glucopyrano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…It is usually used to predict the migration and distribution of compounds in the environment, the accumulation and expansion in organisms, and the study of compound activity (or toxicity), which has special significance in environmental and medical research. , Herein, ChemBioDraw (Ultra 14.0) software could be used to estimate the log P value of 4a – 4g . The water solubility of the dried 4a – 4g was measured at 25 °C …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is usually used to predict the migration and distribution of compounds in the environment, the accumulation and expansion in organisms, and the study of compound activity (or toxicity), which has special significance in environmental and medical research. , Herein, ChemBioDraw (Ultra 14.0) software could be used to estimate the log P value of 4a – 4g . The water solubility of the dried 4a – 4g was measured at 25 °C …”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that the phase behaviors should greatly depend on hydrophilic sugar head and hydrophobic alkyl chains. , For example, it has been shown that increasing the alkyl chain length leads to higher thermal stability of the thermotropic and lyotropic phases, because long-chain alkyl glycosides have stronger van der Waals interactions and require more energy to melt them. ,, In recent years, the application of sugar-based nonionic surfactants has become more widespread, which greatly increases the possibility of them entering the environment and industrial and household waste . More importantly, their biological and industrial importance has encouraged the development and application of many synthetic glycolipids and their derivatives; the well-known APGs should be the most important, which have been found to be used in many fields. , It is reported that although long-chain APGs and AGs with 1,2-cis or 1,2-trans anomeric pure have high surface activity, they have a fatal weakness, that is, weak hydrophilicity and poor or even no water solubility, which has brought great limitations to its commercial application . Therefore, the research on their preparation, characterization, derivatization, reconstruction, physicochemical characteristics, and application should be crucial .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the parent surfactants, it is well known that the length and hydrophobicity of the alkyl chains vary the general physical and surfactant properties [35,36] such as solubility in water, liquid crystal behavior, critical micelle concentration (CMC), micelle size, affinity for SA, and so on. [37] By extension, these properties are expected to the extend to the peptide conjugates (to a greater or lesser extent, depending on peptide size and placement) with clear potential to substantially affect, in a tunable way, solubility in presence of SA, PK/PD behavior in vivo, receptor affinity and kinetics, protease resistance, permeability across mucosal membranes, and so on. It was not feasible to investigate all of these aspects at this stage of preliminary proof-of-concept…”
Section: Pth Analog Designmentioning
confidence: 99%
“…The objective with these modifications was to demonstrate the effect of varying the chain length of the surfactant as this is known to affect the CMC, solubility and micellar behavior of such surfactants. [36,37] The duration of action in vivo is anticipated to vary with chain length, with longer chains expected to show slower uptake and tighter binding to SA, resulting in lower Cmax and longer T 1/2 , although this has not yet been evaluated in detail for this series due to funding limits. Further variation in physical properties and PK profile are possible by variation of the surfactant head group (e.g., mono vs disaccharide; α or β configuration) and alkyl tail group functionalization.…”
Section: In Vitro Characterizationmentioning
confidence: 99%